Α Cultural History of Gesture from Antiquity to the Present Day, with an introduction by Sir Keith Thomas, edited by Jan Bremmer and Herman Roodenburg - ΚΥΡΚΙΝΗ ΑΝΑΣΤΑΣΙΑ (Μνήμων, 1996)
Δεν παρατίθεται περίληψη.